A coronary artery fistula having connection between 2 coronary arteries and the left ventricle: A case report. Issue 45 (November 2017) - Kim, Chang-Yeon; Choi, Ji Yong; Kim, Kee Sik
Abstract: Rationale: Cases of coronary artery fistula having a connection with the cardiac cavity are rare. Here, we report a case in which 2 coronary arteries empty into the left ventricular cavity together. Patient concerns: A 63-year-old woman who was diagnosed as having hypertension 20 years prior presented with dyspnea. Diagnoses: The coronary angiography revealed coronary artery fistula. Interventions: Chest X-ray showed pulmonary edema. Transthoracic echocardiography revealed moderately decreased left ventricular (LV) function and increased LV end-diastolic volume and mass index. Coronary angiography and cardiac computed tomography revealed that 2 coronary arteries joined together at the distal end and directly drained into the left ventricular cavity bypassing the myocardial capillary vessels. We started medical treatment for heart failure with an angiotensin-converting-enzyme inhibitor, loop diuretic, and spironolactone. Outcomes: The pulmonary edema improved rapidly. The patient did not experience dyspnea after discharge, and follow-up echocardiography showed improved cardiac function. Main lesson: Coronary artery fistula could be found incidentally on coronary angiography performed for varied reasons. Physicians must decide carefully whether the fistula needs to be treated in view of the clinical context. Abstract : Supplemental Digital Content is available in the text